Performance modelling of the Darrieus wind turbine - Thuzar Mon; Supakit Worasinchai (My University, 2021)
Three-dimensional numerical investigation of the Darrieus wind turbines equipped with different aerofoils is presented in this paper. In the modelling, the computational domain was divided into three different domains and they are blade, rotor, and tunnel domains. A cylindrical domain was created to cover the blade area so that a fine mesh can be applied. The Computational Fluid Dynamics (CFD) was employed to solve and analyze the flow field around the turbine. The Menter Shear Stress turbulence model was chosen in this investigation. Boundary conditions applied were velocity at the inlet, pressure opening at the outlet, and symmetry on other sides. Comparison of simulation results and experiments showed good agreement. The investigation of the effects of the rotor solidity and the aerofoil shape was performed. The simulation results reveal that the aerofoil shape has a significant impact on the turbine performance. For the rotor solidity of 0.7, the change from the NACA section to the S1046 leads to a reduction of power at low tip speed ratios but the performance improvement is observed when the tip speed ratio is greater than 1.5. With the lower solidity of 0.375, the effects of the aerofoil change is less pronounced at low tip speed ratios. Nevertheless, the maximum power coefficient increases for both cases. Further analysis shows that the S1046 is less sensitive to the wind speed change and is promising in the urban application where the wind speed is relatively low.
Keywords: Solidity; Tip-speed ratio; Wind Energy Research and Development